Co-reference, Thematic, and Network Analysis of a Selected Hungarian Poem and Its English Translation (Füst Milán: A szőlőműves / The Vine-Dresser) - Boda, István Károly; Tóth, Erzsébet (Acta Cybernetica, 2025)
In our paper we present a parallel co-reference analysis of the Hungarian poem A szőlőműves (The Vine-Dresser) by Milán Füst and its English translation. We explore the textual world of the poem and compare the Hungarian and English texts using formal linguistic tools based on semiotic textology. We also reveal the possible differences between the original Hungarian text and its English translation. The results of the analysis prove that co-reference analysis devised and elaborated by János S. Petőfi can be effectively applied in a polyglot environment. We also introduce the hypertext implementation of the co-reference analy-sis of the selected poetic texts in a form of a web page. We would like to show that this has many practical advantages, for example, the analysis and its results can be transparent, accessible, and verifiable to everyone. In addition, the created web page provides additional aspects for the analysis. For example, considering the poetic text as a network, we can investigate whether the scale-free feature is also relevant in the textological environment – as it can be experienced in many other areas of reality.